Dysregulation of Diurnal Cortisol Secretion Affects Abstinence Induction during a Lead‐in Period of a Clinical Trial for Depressed Cocaine‐Dependent Patients. (January 2014) - Raby, Wilfrid Noel; SanFilippo, Lisa; Pavlicova, Martina; Carpenter, Kenneth M.; Glass, Andrew; Onyemekwu, Chukwudi; Roginek, Eric; Nunes, Edward V.
Abstract : Background and Objective: Hypothesizing that stress dysregulation may worsen cocaine dependence, we investigated the effect of diurnal cortisol secretion profile, suppression of cortisol secretion, and total cortisol secretion on retention, abstinence‐based voucher earnings, days of cravings, and mood status of participants at the end of a 2‐week medication‐free lead‐in prior to randomization in a clinical trial of mirtazapine (60 mg vs. placebo) for depressed cocaine‐dependent patients. Methods: We measured saliva cortisol levels at 9 AM, 2 PM, and 5 PM on the first two consecutive days of a 2‐week medication‐free lead‐in period. Results from saliva samples were used to estimate the total daily level of cortisol, the diurnal profile of secretion (typical vs. atypical), and response to dexamethasone suppression (.1 mg). Seventy‐seven patients collected saliva samples at baseline, and 65 (85%) were suitable for profile analysis. Results: Patients with typical profiles (52%) collected significantly more abstinence‐based voucher earnings during the lead‐in ( U  = 299.50, p  = .025). Diurnal secretion profile did not significantly affect mood status, days of craving, or retention. There were no significant effects of suppression of cortisol secretion or of total cortisol levels on any outcome measures. Conclusion: In a subgroup of cocaine‐dependent patients, deviation of cortisol secretion away from the homeostatic diurnal pattern was associated with reduced success at achieving early abstinence, an important determinant of treatment success. (Am J Addict 2014;23:1–6)